Characterization and study of CdS quantum dots solar cells based on Graphene-TiO2 nanocomposite photoanode - Mnasri, G.; Mansouri, S.; Yalcin, M.; El Mir, L.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2020)
The CdS sensitized quantum dots solar cells graphene oxide-titanium dioxide (GO-TiO2) nanocomposite photoanode have been fabricated using a solvent modified successive ionic layer adsorption and reaction method. The graphene has a large absorption band of white light for that we have used graphene for graphene-TiO2 nanocomposite. The graphene-TiO2 nanocomposite photoanode has been deposited onto FTO using doctor blade method as a photoanode to obtained a negative capacitance. Quantum dots could increase the efficiency of solar cells and make it possible to capture the energetic electrons and transmit them to the material type acceptor such as the TiO2 has been used for severely photovoltaic cells (PV-cells). From a single absorbed photon upon relaxation of the primary electron-hole pair excited by light the GO can create a lot number of pairs of electronhole. So that the excess excitation energy will not be lost in the form of phonons or heat, The GO transfers the excess excitation energy to other carriers to produce hot charge carriers in the conduction band of the acceptor material. The particular behavior from the positive to negative capacitance due to the injection of carriers charges from the FTO electrode into TiO2 has been confirmed by the experimental measurement of the capacitance versus voltage (C-V). We have simulated the I-V and P-V characteristics of equivalent circuits of the solar cell. By using the method of Newton-Raphson the studied models are then employed through the involvement by writing matlab programs.
Keywords: Solar cell; CdS quantum dots; GO-TiO2 photoanode; Inductive-capacitive materials; Matlab/Simulink; Newton-Raphson